Effect of light intensity and fertiliser levels on the stock plants of chengal (Neobalanocarpus heimii) and rooring of its subsequent cuttings - Aminah, H; Naimah, C.L.; Raja Barizan, R.S.; Mohd Noor, M (Universiti Kebangsaan Malaysia, 2013)
A factorial experiment of three light intensities and three fertiliser levels was carried out on the potted seedlings of Neobalanocarpus heimii as stock plants for subsequent rooting of cuttings. Light intensities used were 25%, 50% and 100% of the open sunlight and the fertilizer levels were 0 g, 1 g and 2 g plant-1 month-1. Results of 11 months after potting showed that the stock plants treated with 1 g and 2 g fertilizer had significantly better height and diameter increments than those without fertilizer in all light intensities tried. On the other hand, no significant effect of light intensity was obtained in height and diameter increments of the stock plants. Survival of stock plants of more than 86% was obtained in all light intensities tried with or without fertilizer application. Test on rooting of subsequent cuttings showed that light intensity of 25% and 0 g fertiliser, to stock plants gave the highest rooting percentage (73%) and the number of roots (2.0). The general trend showed that rooting decreased to below 60% when intensity of light was increased. In terms of size, cuttings with diameter between 1.2 mm and 2.3 mm is recommended as it yielded rooting of 65% to 75%. For practical application, a combination of 25% light intensity and 1 g of fertilizer plant-1 month-1 can be applied to the stock plants to maintain their healthy growth for continuous production of cutting materials for rooting